2014
DOI: 10.1371/journal.pone.0108532
|View full text |Cite
|
Sign up to set email alerts
|

An Extract of Pomegranate Fruit and Galangal Rhizome Increases the Numbers of Motile Sperm: A Prospective, Randomised, Controlled, Double-Blinded Trial

Abstract: Pomegranate fruit (Punica granatum) and galangal (Alpinia galanga) have separately been shown to stimulate spermatogenesis and to increase sperm counts and motility in rodents. Within traditional medicine, pomegranate fruit has long been used to increase fertility, however studies on the effect on spermatogenesis in humans have never been published. With this study we investigated whether oral intake of tablets containing standardised amounts of extract of pomegranate fruit and powder of greater galangal rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
3
17
0
1
Order By: Relevance
“…For example, in rats, the formulation of hydro‐alcoholic extracts of L. meyenii and F. tessmannii could increase spermatogenesis and testosterone level much more when administered together (Lembe et al, ). Similarly, men with poor semen quality who had received standardised extracts of the combination of Punica granatum and Alpinia galanga showed increased total number of motile spermatozoa after three months of daily treatment (Fedder et al, ). All these interesting findings are expected to drive the development of new botanical medicines for the treatment of male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rats, the formulation of hydro‐alcoholic extracts of L. meyenii and F. tessmannii could increase spermatogenesis and testosterone level much more when administered together (Lembe et al, ). Similarly, men with poor semen quality who had received standardised extracts of the combination of Punica granatum and Alpinia galanga showed increased total number of motile spermatozoa after three months of daily treatment (Fedder et al, ). All these interesting findings are expected to drive the development of new botanical medicines for the treatment of male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit study of Fayed et al (2012), it was reported that a supplementary diet with pomegranate peel in different concentrations (0.5%, 1.0% and 1.5%) for eight weeks raised semen volume, motility and total number of spermatozoa, while the morphological abnormal and dead/live sperm ratio were decreased. On the other hand, in human the daily consumption of tablets of P. granatum extract for 3 months resulted in a significant increase of the sperm motility and volume (Fedder et al, 2014). According to Leiva et al (2011), daily administration of 500 mg/kg pomegranate extract to rats exposed to lead poisoning for A: Control group and 1 ml % 0.5 carboxymethyl cellulose (CMC) B: animals treated with 25 mg/kg/day pomegranate extract + 1 ml % 0.5 carboxymethyl cellulose (CMC) C: animals treated with 50 mg/kg/day pomegranate extract + 1 ml % 0.5 CMC D: animals treated with 100 mg/kg/day pomegranate extract + 1 ml % 0.5 CMC.…”
Section: Discussionmentioning
confidence: 99%
“…galangal in male infertility. The treatment with the tablets contained the extracts of greater galangal rhizome ( A. galangal ) and pomegranate fruit in a clinical study and increased the total number of motile spermatozoa by 62% compared with the placebo (Fedder et al, ). Also, oral administration of A. galangal extract (100 mg kg ‐1 day ‐1 , for 90 days) has been reported to increase the sperm motility and sperm counts in male mice without any spermatotoxic effect (Ravichandran, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of 3 months, semen analysis was done for each patient again. Semen samples were kept at or above room temperature (max 30◦C) (Fedder et al, ) and were analysed within 1 hr of sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation